Of Runes and Sagas : Perspectives on Liquidity Stress Testing Using an Iceland Example - Cihak, Martin; Ong, Li. (Washington, D.C. : International Monetary Fund, 2010)
The global financial crisis revealed weaknesses in the stress testing exercises performed on financial institutions and systems around the world. These failures were most evident in the area of liquidity risk, where now-obvious vulnerabilities were left largely undetected, with stress tests having largely focused on solvency risk. This paper uses publicly available data from a now-defunct bank in Iceland, where liquidity shocks were immense, to demonstrate how a combination of stress tests of the various risks would have provided a clearer picture of existing vulnerablities. We show that, ultimately, stress test models do not necessarily need to be complex or overly sophisticated. Basic stress tests, using appropriate assumptions and shocks, could reveal key areas of risk to inform contingency planning. The liquidity stress test templates used in this paper are included.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet